2020
DOI: 10.1371/journal.pone.0230954
|View full text |Cite
|
Sign up to set email alerts
|

Can silicon applied to correct soil acidity in combination with Azospirillum brasilense inoculation improve nitrogen use efficiency in maize?

Abstract: Alternative management practices are needed to minimize the need for chemical fertilizer use in non-leguminous cropping systems. The use of biological agents that can fix atmospheric N has shown potential to improve nutrient availability in grass crops. This research was developed to investigate if inoculation with Azospirillum brasilense in combination with silicon (Si) can enhance N use efficiency (NUE) in maize. The study was set up in a Rhodic Hapludox under a no-till system, in a completely randomized blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Besides, there were high correlations (0.89-0.98) between Si and nutrient concentrations in the diagnose leaf. Silicon fertilization has been shown to increase N uptake and efficient use in several crops (Galindo et al 2020;Oliva et al 2020). Xu et al (2018) reported a 10 to 18% increase in leaf N concentration of legume and grass species amended with 210 kg ha −1 N plus 40 kg ha −1 H 4 SiO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there were high correlations (0.89-0.98) between Si and nutrient concentrations in the diagnose leaf. Silicon fertilization has been shown to increase N uptake and efficient use in several crops (Galindo et al 2020;Oliva et al 2020). Xu et al (2018) reported a 10 to 18% increase in leaf N concentration of legume and grass species amended with 210 kg ha −1 N plus 40 kg ha −1 H 4 SiO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Silicon (Si) is the second most abundant element after oxygen in the Earth’s crust, comprising approximately 29% (28.8% wt) of the Earth’s crust [ 1 , 2 , 3 ]. Although Si is considered a quasi-essential element rather than a plant nutrient, it is increasingly being applied in agricultural systems worldwide [ 2 , 3 , 4 , 5 ]. Silicon content in the soil ranges from almost 1 to 45% depending on soil types [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Azospirillum brasilense also has been reported to reduce abiotic and biotic stresses by inoculant × plant × environment interactions (Bashan & de-Bashan, 2010;Salvo et al, 2018). Literature on the interaction between PGPR inoculation and Si application has increased over the last few years (Chandrakala et al, 2019;Etesami, 2018;Galindo et al, 2020aGalindo et al, , 2020bMahmood et al, 2016). Etesami (2018) concluded the associated use of PGPR and Si can be a sustainable and powerful strategy to improve plant growth under adverse conditions.…”
Section: Core Ideasmentioning
confidence: 99%
“…Literature on the interaction between PGPR inoculation and Si application has increased over the last few years (Chandrakala et al., 2019; Etesami, 2018; Galindo et al, 2020a, 2020b; Mahmood et al., 2016). Etesami (2018) concluded the associated use of PGPR and Si can be a sustainable and powerful strategy to improve plant growth under adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation